Trans-cis inter-conversion of blankophur BBU - Ung, Paul Y.; Lim-Sylianco, Clara Y. (Quezon City Department of Chemistry, College of Arts and Sciences, University of the Philippines Diliman, 1967)
Fluorescent brightening agents are aromatic substances which give colorless solutions but which are strongly fluorescent when in aqueous solutions. The greenish blue to reddish violet fluorescence emitted by the brightener appears as a brilliant white shade when combined with the yellow color inherent of the substrate.
Fluorescent brighteners are mostly coumarin and stilbene derivatives. Unlike coumarin brighteners, dilute solutions of stilbene brighteners are very sensitive to light. This instability is caused by the conversion of the strongly fluorescing tarns-form, under the action of light, into the non-fluorescing cis-form. Such a rearrangement occurs intramolecularly. Experimental data, usin Blankophor BBU, show that the trans-cis interconversion is reversible and that the rate s dependent not only on the brightener concentration but also on the intensity of the incident radiation.
Thesis (Bachelor of Science in Chemistry)--University of the Philippines Diliman, May 1967.
Keywords: Optical brighteners